From Brand to Space: Experiential Pedagogy and Sensory Cognition in Interior Architecture Education (Architecture Image Studies, 2025)
This study examines how undergraduate interior architecture students translate brand identity into spatial experience through multisensory and morphological strategies within a reflective design-studio environment. Despite the increasing emphasis on experiential retail design in professional practice, limited academic research addresses how such sensory and narrative competencies are cultivated pedagogically. Bridging this gap, the study proposes an interpretivist framework that links brand semantics with experiential cognition in design education. Adopting a qualitative, multi-layered methodology, the research analyzes 15 flagship-store projects developed during the Interior Architecture Project II course at Istanbul Aydın University. Data were collected from conceptual diagrams, renderings, and instructor feedback, and analyzed through visual, morphological, and sensory coding. Findings reveal that students moved beyond representational branding toward embodied spatial storytelling, using light, form, color, and material as emotional and cognitive mediators. The results demonstrate that reflective and experiential learning fosters sensory awareness, conceptual depth, and narrative competence in design processes. The study contributes to interior architecture pedagogy by evidencing how neuro aesthetic and multisensory approaches can enrich cognitive-emotional integration, advancing both design education and practice. The proposed framework, supported by 15 design-studio cases, provides empirical grounding for integrating sensory-based pedagogy into interior architecture curricula.